Meta-Analysis on the Efficacy and Safety of Hyperbaric Oxygen as Adjunctive Therapy for Vascular Dementia - You, Qiang; Li, Lan; Xiong, Su-qin; Yan, Yu-fen; Li, Dan; Yan, Na-na; Chen, Hong-ping; Liu, You-ping (Frontiers in Aging Neuroscience, 2019)
Background: Vascular dementia (VD) is a common type of disease in the elderly. Numerous clinical trials have suggested that hyperbaric oxygen was effective and safe complementary therapies for aging-related disorders. However, there is no systematic evidence regarding HBOT for the treatment of VD. Therefore, we performed a meta-analysis to value the clinical efficacy and safety of HBOT in treating VD. Methods: We methodically retrieved the clinical studies from eight databases (PubMed, The Cochrane Library, Embase, Web of Science, Sino-Med, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and WanFang) from their inception to November 2018. RevMan 5.3.5 was used for quality assessment and data analysis. Stata 15.1 was employed for publication bias detection. Results: Twenty-five randomized clinical trials involving 1954 patients met our inclusion criteria. These articles researched the HBOT + Oxiracetam + CT versus Oxiracetam + CT(n=13), HBOT + Butylphthalide +CT versus Butylphthalide + CT(n=5), HBOT + Donepezil + CT versus Donepezil + CT(n=4), HBOT + Nicergoline + CT versus Nicergoline + CT (n=2) and HBOT + CT versus CT(n=1). The results indicated that additional HBOT strikingly improved the Mini-Mental State Examination (MMSE) (MD = 4.00; 95% CI=3.28-4.73; P＜0.00001), the Activities of Daily Living (ADL) (MD = -5.91; 95% CI=-6.45, -5.36; P＜0.00001), BADL (MD = 13.86; 95% CI=5.63- 22.10; P=0.001), and increased the total efficacy rate (OR =4.84, 95% CI= 3.19-7.33, P< 0.00001), and the adverse events rates were not statistically significant between the two groups (OR =0.85, 95% CI= 0.26-2.78, P= 0.79). Conclusion: In view of the effectiveness and safety of HBOT, the present meta-analysis suggested that HBOT can be recommended as an effective complementary therapy for the treatment of VD.